2023
DOI: 10.1080/22221751.2023.2209208
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in SARS-CoV-2 variant nsp6 enhance type-I interferon antagonism

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) continues to evolve after its emergence. Given its importance in viral infection and vaccine development, mutations in the viral Spike gene have been studied extensively; however, the impact of mutations outside the Spike gene are poorly understood. Here, we report that a triple deletion (ΔSGF or ΔLSG) in nonstructural protein 6 (nsp6) independently acquired in Alpha and Omicron sublineages of SARS-CoV-2 augments nsp6-mediated antagonism of type-I in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…We show that these two variants differ in their ability to inhibit the interferon response in individuals infected with SARS-CoV-2. This is supported by gene expression and interactome analyses, which corroborate the findings of previous researchers that studied the interferon response in tissue culture samples and animal models [43].…”
Section: Discussionsupporting
confidence: 89%
“…We show that these two variants differ in their ability to inhibit the interferon response in individuals infected with SARS-CoV-2. This is supported by gene expression and interactome analyses, which corroborate the findings of previous researchers that studied the interferon response in tissue culture samples and animal models [43].…”
Section: Discussionsupporting
confidence: 89%
“…CD63, as a tetraspanin protein, mainly distributes on the cell membrane and endosome membrane ( 37 , 57 ). In contrast, NSP6 is a multi-transmembrane protein that localizes on the ER membrane and in the perinuclear space ( 24 , 58 ). After co-transfecting GFP-tagged NSP6 (NSP6-GFP) with CD63-RFP, we found that most CD63 proteins were redistributed from the membrane surface into the cytoplasm and significantly co-localized with NSP6 proteins ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the T429I substitution in non-structural protein-4 (NSP4) enhances replication capacity, improves evasion mechanisms against host immune responses, and augments the infectivity of SARS-CoV-2 [ 75 ]. Similarly, the triple deletion ΔSGF in non-structural protein-6 (NSP6) significantly impacts host-pathogen interactions, resulting in discernible alterations in the virulence profile of SARS-CoV-2 [ 76 ].…”
Section: Discussionmentioning
confidence: 99%